Two new species of Rhodacaridae (Mesostigmata: Rhodacaroidea) from Iran - Castilho, Raphael C.; Jalaeian, Mahdi; de Moraes, Gilberto J. (Zootaxa, 2012)
Multidentorhodacarus saboorii n. sp. and Rhodacarellus iraniensis n. sp. (Acari: Mesostigmata: Rhodacaroidea: Rhodacaridae) are described and figured. These are the first descriptions of Rhodacaridae mites from Iran.